Criteria for low von Willebrand factor diagnosis and risk score to predict future bleeding. (24th January 2021) - Atiq, Ferdows; Wuijster, Esmee; de Maat, Moniek P.M.; Kruip, Marieke J.H.A.; Cnossen, Marjon H.; Leebeek, Frank W.G.
Abstract: Background: Important diagnostic and clinical aspects of moderately reduced von Willebrand factor (VWF) levels are still unknown. There is no clear evidence which cutoff value (0.50 vs 0.60 IU/ml) should be used to diagnose "low VWF." Also, the incidence of bleeding after the diagnosis has been made, and risk factors for bleeding are unknown yet. Objectives: To investigate the incidence of postsurgical bleeding, postpartum hemorrhage (PPH), and traumatic and spontaneous bleeding after low VWF diagnosis, and to develop a risk score to predict future bleeding. Methods: We performed a cohort study in patients with historically lowest VWF levels of 0.31 to 0.60 IU/ml. Clinical data of patients were retrospectively collected. Results: We included 439 patients with low VWF. During a follow‐up of 6.3 ± 3.7 years, 259 surgical procedures, 81 deliveries, and 109 spontaneous and traumatic bleeding episodes were reported. The incidence of postsurgical bleeding was 2.7%, whereas 10% of deliveries was complicated by PPH. Overall, 65 patients (14.8%) had bleeding requiring treatment, which was not different between patients with historically lowest VWF levels of 0.31–0.50 and 0.51–0.60 IU/ml ( p = .154). Age <18 years, abnormal bleeding score at diagnosis, and being referred for bleeding symptoms at the time of diagnosis were independent risk factors for bleeding during follow‐up, and therefore included in the risk score. Conclusions: The cutoff value of low VWF diagnosis should be set at 0.60 IU/ml. Furthermore, a risk score is developed to identify individuals with a high risk for bleeding after low VWF diagnosis.